TREN PENELITIAN OPTION PRICING: ANALISIS BIBLIOMETRIS - Yusiana, Rennyta; Chandra, Dicky; Sari, Maya (Program Studi Manajemen Fakultas Ekonomi Universitas Siliwangi, 2023)
The purpose of this research is to present a comprehensive overview of options pricing research and to demonstrate existing themes in the field. This research also tries to provide direction to academics in determining option prices in the future. The method used is bibliometric analysis. This analysis includes 5,367 papers from the Scopus database accessed over a 38-year period (1985-2023) and published in the top 50 finance and economics, econometrics, and financial journals. This number dropped to 913 articles after using the keyword “option pricing” as the primary search term in the “title, abstract, keywords” column. Tabular and visual representations of this analysis indicate that options pricing is a topic that has been thoroughly studied, but the sharp increase in the number of publications (56) for 2015 indicates that interest in this area is expanding. Additionally, affiliate figures show that most of the research was conducted in the United States, with China coming in second. This suggests that there may be potential to investigate option pricing in other countries. This article offers a thorough and complete review along with possible implications for future research.